The Effectiveness of Differentiated Instruction in Improving Bahraini EFL Secondary School Students in Reading Comprehension Skills - Saleh, Ahmed Hussein Ahmad Eid (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
This study aimed at investigating the effectiveness of Differentiated Instruction (DI) in improving reading comprehension skills in the EFL secondary stage in Bahrain. The study adopted the quasi-experimental research design using thirty-six 2nd year secondary students to be the study participants. The participants were divided into two groups: an experimental group that received the (DI) training and a control group that received the conventional way. A reading comprehension skills questionnaire and a pre-post EFL reading comprehension test was used in the study to collect the data. Results showed that the experimental group outperformed the control group in the EFL reading comprehension test. The findings indicated that the DI strategies helped to develop students’ EFL reading comprehension skills. In addition, it revealed that using various materials for teaching reading comprehension skills to match students' different needs and abilities helped enhance their reading comprehension proficiency. A number of recommendations and suggestions for further research was presented.